Comparison of fatigue criteria for combined bending-torsion loading of nitrided and virgin specimens - Major, S.; Papuga, J.; Hornikova, J.; Pokluda, J. (Проблемы прочности, 2008)
This work deals with fatigue life of plasma-nitrided and virgin specimens made of a low-alloy high strength steel. Specimens were subjected to an in-phase combined bending-torsion loading. The plasma-nitrided specimens exhibited a significantly improved fatigue resistance. The criterion proposed by McDiarmid was found to be the most precise in the fatigue life prediction fo r virgin specimens. On the other hand, the Matake criterion was the most successful fo r nitrided specimens.